An open vendor agnostic fog computing framework for mission critical and data dense applications - Chirindo, Tasimba Denford David (Department of Electrical Engineering, 2019)
Digital innovation from the Internet of Things (IoT), Artificial Intelligence, Tactile Internet and Industry 4.0 applications is transforming the way we work, commute, shop and play. Current deployment strategies of these applications emphasize mandatory cloud connectivity. However, this is not feasible in many real-world situations particularly where data dense and mission critical applications with stringent requirements are concerned. Cloud computing offers unlimited on-demand computing, storage and networking power for industry to leverage. However, as its scope and scale continues to expand, its limitations like high latency, accessibility, security and compliance shortcomings prevent its greater use and applicability particularly in scenarios where real-time communication and the quality of rapid computing delivered is a necessity. Fog computing hopes to bridge this gap by introducing an intermediary computing layer between end users and the cloud. At present, architectures for fog computing exist in specialized areas with current implementations being proprietary, vendor-locked and requiring dramatic and non-transferable changes to hardware and software to meet vendor requirements. Moreover, fog computing is still quite a recent area which makes the state of the art incipient regarding architecture definitions, middleware and real-world implementations. There is therefore an urgent need for standardization of these technologies. This is of paramount importance as otherwise, there will exist multiple and not necessarily compatible solutions which could lead to a fragmented marketplace that would fail to grow. In an effort to address these limitations in current fog architectures, this dissertation proposes and implements a novel fog computing architecture that aligns the reference architectures from a leading industry consortium, OpenFog, and a leading standards setting organization, the European Telecommunications Standards Institute (ETSI). This cooperation framework from industry, academia and regulatory institute aims to make it easier for both application developers and infrastructure solution providers to develop towards a common, open and interoperable fog computing environment. The proposed framework has the following attributes: modular, plug-in design, generic, open, standards compliant, vendor agnostic and runs on high volume standard hardware whilst preserving the benefits offered by public clouds such as containerization, virtualization, orchestration, manageability and efficiency. Moreover, for the various stakeholders in the fog value chain where it is key to strike a balance between information technology and business operations, this thesis tenders insights and best practices to help achieve these multiple and sometimes competing goals. The proposed framework was implemented in a testbed environment made up entirely of free and open source software, therefore creating a convenient point of departure for further research by others. Two geographically distributed fog node data centres and a cloud management and orchestration tool were setup in the testbed. While this evaluation framework and practical implementation demonstrated proof of concept, further evaluations were conducted to benchmark the performance against existing alternative solutions. These evaluations were based on a prototype industrial IoT application that was deployed on the testbed to evaluate the impact of the Open Vendor Agnostic Fog Framework (OVAFF) solution on application performance. The implementation showed that the proposed OVAFF solution is feasible, implementable and supports distributed edge cloud data centres. Results from the prototype application showed that OVAFF can extremely provide up to tenfold throughput and ultra-low latency, jitter and packet loss rate better than the remote clouds. Moreover, there is more superiority exhibited by the OVAFF for other non-performance based attributes like data reduction, compliance and geographical locality of control. In addition, the results also pointed towards the viability of open business models like federated infrastructure sharing and a fog market place in the fog ecosystem. Finally, this thesis tackled the highlighted open challenges in current fog systems such as orchestration, distribution, tiering, heterogeneity and resilience; which were outlined in the research motivation and problem definition.